« Fatta fedelmente volgarizzare ». Documents traduits et insérés dans la Nuova cronica de Giovanni Villani (Florence, XIV siècle). - Rabiot, Jérémie (Médiévales)
This paper focuses on the translation into vernacular and the transcription of Latin documents in the Nuova Cronica, a history of the world and of the city of Florence written in the fourteenth century by the chronicler and merchant Giovanni Villani. It studies the objectives and principles of translation adopted here, and highlights the political and social issues that led the author to receive, translate, and copy official documents (papal bull, exchanges of Chancery, or alliance treaty). It therefore aims to link these facts with the increase of vulgarizations of communal statutes, at a time when political communication in vernacular was becoming more widespread in the communes of Italy.